Pourquoi vient-on voir l’Everest ? Représentations collectives et pratiques touristiques dans la région du Khumbu - Etienne Jacquemet (Revue de Géographie Alpine)
Beyond a simple fascination with the height of the summit itself, this article aims to explore the various sources of motivation that lead tens of thousands of visitors to come to the Everest (Khumbu) region of Nepal every year. Drawing on an analysis of collective representations by tourists, this article will show that the Khumbu region combines various principles of heterotopias (Foucault, 1967). This region, long unexplored and closed to outsiders, and its landscapes infused with religiosity, attracts tourists because it is still largely seen as a genuine lost paradise. These elements are conducive to the processes of physical and mental renewal, in addition to social distinction which allows trekkers –in a more or less conscious, temporary, or performance-based manner– to push themselves to their limits. The popularity and increasing openness of the Everest region and its inhabitants to globalisation, which could theoretically call into question the meaning and very principles of this heterotopia, do not seem to affect the experience of trekkers, despite the fact that their practices are based on a complete break with the places and time frames of their everyday life.